Investigation of Concepts for Integrated Diffuser and Volute Systems for Packaging and Performance - McLaughlin, Laura Kate (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2023)
Large scale, high pressure ratio (PR) centrifugal compressors are commonly made up of a radial impeller with a vaned diffuser. In research to date, the majority of research and design has focused on extending the operating range or improving the compressor efficiency. However, a cost and weight saving can be achieved by reducing the compressor dimensions. This is a study of 15% radially reduced vaned diffuser and volute components, aiming to reduce the overall radial dimensions of the compressor without any sacrifice of compressor performance at design point (DP). The vaned diffuser study parameterized a diverging endwall diffuser concept and optimized it to achieve a similar performance within a reduced radial outlet dimension. A metamodel assisted Multi Objective Genetic Algorithm (MOGA) method has been used. A numerical approach has been used to investigate how the flow physics within the diffuser passage changed with the new geometry and detailed experimental measurements have been used to validate the numerical approach. The measured performance showed that the same efficiency performance was achieved within a 15% radially reduced diffuser passage using the diverging endwall concept. Despite not being one of the goals of the optimization procedure, an extension of the stable operating range of 36% and 20% at the highest speed condition was achieved for the scaled and optimized designs, respectively. The diffuser component study also focuses on low flow rate operating points, necessitating the use of an Unsteady Reynolds Averaged Navier-Stokes (URANS) approach to analyse the flow. Detailed scrutiny of the flow field revealed a secondary flow feature in the diffuser passage which resulted in higher diffuser passage losses at DP but stabilised the flow as it developed for lower mass flow rate operating points. The volute study considered the compressor design operating point and implemented a fixed 15% radial reduction to the radial extent of the volute component. The volute spiral was carefully parameterized and a Design of Experiments investigation was set up to quantify the impact of these parameters on the performance of the volute and the upstream components. The resulting analysis generated understanding of the underlying flow physics responsible for the performance changes. The study found that a 15% reduction could be applied to the diffuser and volute components while achieving 99.9% of the baseline compressor total-total efficiency at design point. Although the volute investigation considered design point only, the improvement to circumferential flow uniformity suggests that the best design may achieve an extension to the compressor operating map width.
APPROVED
Keywords: CFD; Compressor; Experimental; Diffuser; Volute; Aerodynamics